A Home-Based Program of Transcutaneous Electrical Nerve Stimulation and Task-Related Trunk Training Improves Trunk Control in Patients With Stroke: A Randomized Controlled Clinical Trial. (January 2015) - Chan, Bill K. S.; Ng, Shamay S. M.; Ng, Gabriel Y. F.
Background . Impaired trunk motor control is common after stroke. Combining transcutaneous electrical nerve stimulation (TENS) with task-related trunk training (TRTT) has been shown to enhance the recovery of lower limb motor function. Objective . This study investigated whether combining TENS with TRTT would enhance trunk control after stroke. Methods . Thirty-seven subjects with stroke were recruited into a randomized controlled clinical trial. Subjects were randomly assigned to any one of the three 6-week home-based training groups: (1) TENS + TRTT, (2) placebo TENS + TRTT, or (3) control without active training. The outcome measures included isometric peak trunk flexion torque and extension torque; forward seated and lateral seated reaching distance to the affected and unaffected side; and Trunk Impairment Scale (TIS) scores. All outcome measures were assessed at baseline, after 3 and 6 weeks of training, and 4 weeks after training ended at follow-up. Results . Both the TENS + TRTT and the placebo-TENS + TRTT groups had significantly greater improvements in isometric peak trunk flexion torque and extension torque, lateral seated reaching distance to affected and unaffected side, and TIS score than the control group after 3 weeks of training. The TENS + TRTT group had significantly greater and earlier improvement in its mean TIS score than the other 2 groups. Conclusions . Home-based TRTT is effective for improving trunk muscle strength, sitting functional reach and trunk motor control after stroke in subjects without somatosensory deficits. The addition of TENS to the trunk augments the effectiveness of the exercise in terms of TIS scores within the first 3 weeks of training.